2016
DOI: 10.14740/jocmr2400w
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review on ICF From 2001 to 2013 in the Nordic Countries Focusing on Clinical and Rehabilitation Context

Abstract: We present a systematic review on International Classification of Functioning, Disability and Health (ICF) used in the Nordic countries from 2001 through 2013, describing and quantifying the development in utilization of ICF, and describe the extent to which the different components of the ICF have been used. A search was conducted in EMBASE, MEDLINE and PsycInfo. Papers from Nordic countries were included if ICF was mentioned in title or abstract. Papers were assigned to one of eight categories covering the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Another review that specifically targeted the use of the ICF in the Nordic European countries found that there was an increase in ICF relevant papers, especially in the fields of neurology, musculoskeletal, and work-related areas. Nevertheless, the authors concluded that there is still a long way to go before ICF is widely used in rehabilitation and clinical settings [11]. Our review, however, differs from and yet complements these previous reviews by focusing specifically on the use of the ICF in EHRs.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Another review that specifically targeted the use of the ICF in the Nordic European countries found that there was an increase in ICF relevant papers, especially in the fields of neurology, musculoskeletal, and work-related areas. Nevertheless, the authors concluded that there is still a long way to go before ICF is widely used in rehabilitation and clinical settings [11]. Our review, however, differs from and yet complements these previous reviews by focusing specifically on the use of the ICF in EHRs.…”
Section: Introductionmentioning
confidence: 89%
“…The ICF complements the International Classification of Diseases (ICD) with information about the impact of a health condition on people's functioning in daily life, such as basic activities of daily living but also participation in various life areas, such as employment [9]. Internationally, the ICF has become increasingly present in recent years [10,11]. Furthermore, functioning as described in the ICF, has been referred to as the third health indicator for monitoring the performance of health systems, next to mortality and morbidity [12].…”
Section: Introductionmentioning
confidence: 99%
“…why did you choose a rating of 2 for the category d450 Walking? [3] Why didn't you select the adjacent response options, e.g. why didn't you select a rating of 1 or 3 instead of a rating of 2?…”
Section: The Consensus Process For Developing the Rating Reference Guidementioning
confidence: 99%
“…Four key topics emerged from a qualitative analysis of the discussion notes: [1] reconciling common clinical terms with the often detailed definitions of the original descriptions of ICF categories [2]; specifying the assumed level of functioning [3]; resolving several different aspects in a given category; and [4] handling the wording of the original definitions of ICF categories which are unfamiliar to Japanese clinicians.…”
Section: Development Of Simple Intuitive Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation